The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.6063/motricidade.6012
|View full text |Cite
|
Sign up to set email alerts
|

Nível de Desempenho Técnico-Tático das Equipas de Voleibol em Escalões de Formação

Abstract: ARTIGO ORIGINAL | ORIGINAL ARTICLE RESUMOO objetivo do estudo foi analisar o nível de desempenho técnico-tático de jogadores de voleibol dos escalões de formação em Santa Catarina. Participaram no estudo 271 jogadores de 24 equipas de voleibol, finalistas do campeonato estadual de 2010, dos escalões mirim, infantil e infanto-juvenil. Os jogos foram filmados e, posteriormente, as ações técnico-táticas analisadas por meio do Instrumento de Avaliação do Desempenho Técnico-Tático no Voleibol. Na análise dos dados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
2
0
3
Order By: Relevance
“…The rebound block, action dominated by the centers in this study, reinforces the finding that it requires a strate-gic and specific position on the court so that if a basket is not converted, the player is in an appropriate position to gain possession of the ball 40 . Thus, it is essential for players of this position to perform well in this action, as this feature requires a better posture of the athlete in moments preceding and/or following the action of the ball towards the basket 41 and prevent the action of the opposing team.…”
Section: Discussionmentioning
confidence: 99%
“…The rebound block, action dominated by the centers in this study, reinforces the finding that it requires a strate-gic and specific position on the court so that if a basket is not converted, the player is in an appropriate position to gain possession of the ball 40 . Thus, it is essential for players of this position to perform well in this action, as this feature requires a better posture of the athlete in moments preceding and/or following the action of the ball towards the basket 41 and prevent the action of the opposing team.…”
Section: Discussionmentioning
confidence: 99%
“…The observation criteria of the performance were the following: adjustment, considering movements and postures performed before, during and after contact with the ball (technical); efficiency, defined as technical execution (technical); decision-making, referring to the choices made in the game (tactical); and effectiveness, as the observable result of the action with regard to its goal (outcome). 32 The volleyball fundamentals were described as: defense—the action performed to prevent the opposite team from scoring, aiming to control the ball for the construction of attack; setting—the action that seeks to facilitate the attack through a pass or a forearm pass; and attack—the action that makes the ball cross the plane of the net to the opponent's side, aiming to score. The study variables, as well as their respective components and indicators are shown in Tables 1, 2 and 3 as proposed by Collet et al 30…”
Section: Methodsmentioning
confidence: 99%
“…Utilizando o indicador de performance de posição final no ranking na competição (Hughes & Bartlett, 2002), percebeu-se que os achados nos aspectos táticos-técnico vão de encontro com os resultados encontrados por Porath et al (2016) que encontraram que o desempenho tático-técnico está relacionado com o rendimento na competição em atletas em formação participantes de um campeonato estadual na região Sudeste do Brasil em 2010.…”
Section: Tabelaunclassified
“…21, n° 2, e083. ISSN 2314-2561 2 Introdução O voleibol é um esporte que exige diferentes elementos para sua qualificação, tais como técnica, tática e demandas físicas que favorecem os aspectos do jogo (Dávila-Romero, Hernández-Mocholí & García-Hermoso, 2015;Lopes, Magalhães, Moreira & Albuquerque, 2016;Porath, Collet, Milistetd, Salles & Nascimento, 2016;Trajković, Milanovic, Sporiš, Milic & Stankovic, 2012;Trajković, Krističević & Sporiš, 2017). Dentre tais elementos, o tático-técnico se destaca como essencial para o sucesso (Peña, Rodríguez-Guerra, Buscà & Serra, 2013), bem como é sugerido que os seus treinamentos sejam monitorados para melhor qualificação (Rodríguez-Marroyo, Medina, García-López, García-Tormo & Foster, 2014).…”
unclassified